2018
DOI: 10.1536/ihj.16-413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Renal Sympathetic Denervation in Patients with Early-Stage Heart Failure Versus Late-Stage Heart Failure

Abstract: SummaryRenal sympathetic denervation (RDN) is currently being investigated in multiple studies of heart failure (HF). Our aim was to assess the safety and effectiveness of RDN in patients with HF, and determine which patients could achieve more beneficial effects of RDN. A total of 17 consecutive patients with HF were enrolled in the study. Clinical symptoms, office blood pressure, and laboratory results were obtained and echocardiography was performed before and 12 months after RDN. Changes from baseline to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…However, 6-minute walk distance is an independent predictor of hospital readmission in patients with chronic heart failure. 37,38) Similar studies also confirmed that the average time of the ivabradine-treated group increased from 328 seconds to 497 seconds (P < 0.0235). 15) The study by Abdel-Salam 32) showed that the proportion of patients with an exercise tolerance of > 6 minutes walking time was significantly higher in the ivabradine group (P < 0.05).…”
Section: Improved Cardiopulmonary Functionsupporting
confidence: 54%
“…However, 6-minute walk distance is an independent predictor of hospital readmission in patients with chronic heart failure. 37,38) Similar studies also confirmed that the average time of the ivabradine-treated group increased from 328 seconds to 497 seconds (P < 0.0235). 15) The study by Abdel-Salam 32) showed that the proportion of patients with an exercise tolerance of > 6 minutes walking time was significantly higher in the ivabradine group (P < 0.05).…”
Section: Improved Cardiopulmonary Functionsupporting
confidence: 54%
“…Renal nerve ablation has been tried in patients suffering from CHF with positive [13][14][15][16] and negative results [17,18]. Reviews and meta-analyses on renal nerve ablation in heart failure suggest a potential benefit of the intervention for patients with heart disease, but there is a lack of larger prospective studies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, included patients had late‐stage heart failure with markedly depressed left ventricular function, as well as high levels of circulating brain‐type natriuretic peptide, catecholamines, and elevated plasma renin activity. It is interesting to note that the lack of improvement after renal denervation might have been related to the elevated‐risk profile of the study population, as recent suggested by a study showing that patients in late‐stage heart failure could benefit less from renal denervation …”
Section: Discussionmentioning
confidence: 94%
“…It is interesting to note that the lack of improvement after renal denervation might have been related to the elevated-risk profile of the study population, as recent suggested by a study showing that patients in late-stage heart failure could benefit less from renal denervation. 24 Compensatory overactivation of autonomic sympathetic nervous pathways is a primary component in the pathogenesis of heart failure secondary to reduced systolic function. [25][26][27] Accordingly, downregulation of abnormally high neurohormonal activity is currently a key therapeutic strategy for patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%